Malnutrition in patients with chronic heart failure. (3rd October 2022) - Weidenhammer, A; Prausmueller, S; Spinka, G; Goliasch, G; Arfsten, H; Pavo, N; Huelsmann, M; Bartko, P
Abstract: Background: Malnutrition is highly common in patients with chronic heart failure and often overlooked. It can accelerate disease progression by activating cytokines, causing autonomic dysfunction and cachexia. If malnutrition is detected early, physicians may be able to identify patients who are at high risk for an adverse outcome. Malnutrition in patients can be assessed according to scores, like the prognostic nutritional index [PNI: albumin (g/L) + 5×total lymphocyte count ×10 9 /L)], controlling nutritional status [CONUT: sum of albumin, cholesterol and lymphocyte count] and the geriatric nutritional risk index [GNRI: (1.489×albumin (g/L)) + 41.7×(weight/ideal weight)]. Objectives: Our aim is to assess the prevalence of malnutrition, expressed by PNI, GNRI and CONUT across the spectrum of HF and to investigate whether these scores are associated with outcome. Methods: In total, 9733 consecutive patients were included in this study. Patients were classified into one of three heart failure subtypes based on guideline diagnostic criteria: reduced (HFrEF; LVEF <40%), mildly reduced (HFmrEF; LVEF 40–49%), or preserved ejection fraction (HFpEF; LVEF ≥50). Malnutrition was assessed based on PNI, GNRI, or CONUT (PNI: Malnutrition<45, absent≥45/ GNRI: <82 severe; 82–91 moderate; 92–98 mild; >98 normal/CONUT: 9–12 severe; 5–8 moderate; 2–4 mild; 0–1 normal). The association between the respective nutritional scores and all-cause mortality was assessed. Results: Of the 9733 patients included, 5680 (58.4%) were diagnosed with HFpEF, 2214 (22.7%) with HFmrEF, and 1839 (18.9%) with HFrEF. Overall, median BMI was 27.5 (IQR 24.5–31.2), 33% of participants were female, and the median age was 70 years (IQR 61–77). 40%, 42%, 63% of patients were defined as malnourished by PNI, GNRI and CONUT, respectively. During a median follow-up time of 3.71 years (IQR 1.56–6.32) a total of 3159 (32.5%) deaths were observed. Malnutrition, as indicated by a low PNI or GNRI and a high CONUT score, was associated with worse survival (PNI: HR 2.53 [2.35–2.71], GNRI: HR 1.60 [1.55–1.66], CONUT: HR 1.841 [1.76–1.9], p<0.001 for all). This association remained significant after adjustment for age, sex, kidney status and NT-proBNP (adj. HR, GNRI: 1.41 (1.35–1.46), PNI: 1.86 (1.72–2.01), CONUT: 1.52 (1.45–1.60) p<0.001 for all). Interaction analysis confirmed that association with mortality was independent from heart failure type for all scores (p=ns for all). Figure1 displays survival curves for nutritional score categories across the spectrum of HF (p<0.001 for all, log-rank test). Conclusion: Malnutrition as assessed by PNI, GNRI and CONUT is common in patients with heart failure. Malnutrition is associated with higher mortality rates, irrespective of type of heart failure and independent from classical confounder models and even NTproBNP. Based on their additional prognostic value, nutritional scores could be included into routine examination to identify high risk patients. Funding Acknowledgement: Type of funding sources: None.